IN HOUSE TRAINING (IHT) PEMBELAJARAN DI MASA PENDEMI DENGAN BLENDED LEARNING SMK N 5 DUMAI - Surya Indrawan; Nur Budi Nugraha; Juni Saputra; Sirlyana Sirlyana (LPPM Universitas Bina Bangsa, 2021)
The revolution in information and communication technology occurred during the last few years. During the COVID-19 pandemic that hit Indonesia, all sectors experienced obstacles, including the education sector which was hampered from carrying out teaching and learning activities. Along with the times, the process of teaching and learning activities in the classroom now has many challenges and demands. One-way learning makes the learning atmosphere boring, it is feared that it will affect students' motivation to study the material, so it is modified into blended learning. This model combines offline and online learning, is student centered, namely students must be active in understanding the material, efficient in time, energy, and place because it can be done anywhere. The methods used in this training activity are lectures and discussions, guidance and training. As a result of this blended learning In House Training, all participants actively participated in this activity and participants gained new insights about blended learning strategies that could be implemented in the classroom teaching process during the COVID-19 pandemic to become more varied and innovative